Friend or foe? Foreign investors and the liquidity of six asian emerging markets (2010)
Studying foreign flows and the liquidity of six Asian markets and the Johannesburg Stock Exchange, we provide evidence of two contrary effects of foreigners on liquidity. On the one hand, foreign trade has a negative but transitory impact on the overall liquidity of the market on a daily basis, consistent with foreign investors demanding liquidity more aggressively than locals and incorporating market-wide information. On the other hand, the overall share of foreign ownership in the market is positively related to improved liquidity, consistent with foreigners improving liquidity provision and sending a positive signal to the market on transparency and monitoring. Overall, the results portray foreign investors as aggressively demanding liquidity in the very short term, but having a lasting positive effect on the liquidity of emerging markets.